THE ROLE OF DOMESTIC TOURISM IN THE DEVELOPMENT OF THE DIGITAL ECONOMY. - Khalikova Lola Nazarovna; Ziyodova Raykhona Jasur kizi (TADQIQOTLAR.UZ, 2024)
Abstract: This article talks about the role and importance of domestic tourism which is considered one of the most important aspects of the tourism industry in the economy of our country. Domestic tourism can contribute to the growth of the gross domestic product, job creation, development of infrastructure and services of the local population, and preservation and promotion of cultural heritage and traditions. There are also proposals for the development of domestic tourism in Uzbekistan.